Accelerated long‐term forgetting in adult patients with genetic generalized epilepsy. Issue 2 (10th December 2021) - Puteikis, Kristijonas; Wolf, Peter; Mameniškienė, Rūta
Abstract: Objective: Accelerated long‐term forgetting (ALF) has been demonstrated among children but not adults with genetic generalized epilepsy (GGE). We investigated (1) how forgetting patterns of verbal and visuospatial material differ between patients with GGE and healthy controls (HCs) and (2) whether ALF is associated with ictal or interictal epileptic activity. Methods: Forty‐two patients with GGE (39, 92.9% experiencing seizures) were compared to 57 HCs in word, logical story, and Rey–Osterrieth complex figure recall tasks by testing after intervals of 30 min and 4 weeks. Ambulatory electroencephalography (EEG) was performed before testing to detect generalized epileptic activity, and patients were asked to document the number of seizures during the 4‐week interval. Results: A two‐way repeated measures ANOVA indicated that individuals with GGE have different forgetting patterns in comparison to HCs in tasks of word (delay by group interaction F 1.5, 142.5 = 4.5, p = .02, η p 2 = .04) and figure ( F 2, 194 = 15.9, p < .001, η p 2 = .14) but not story ( F 1.6 151.1 = .5, p = .58, η p 2 = .005) recall. Last learning trial‐adjusted scores of word recall were comparable between HCs and patients with epilepsy (PWEs) at 30 min ( p = .21) but not at 4 weeks ( p = .006). Individuals with GGE performed worse than HCs in figure recall at 30 min and 4 weeks ( p < .001), with lower performance after the 4‐week interval present only among seizure‐positive and EEG‐positive individuals ( p < .001) during subgroup analysis. Performance on memory tests was unrelated to overall seizure frequency, the number of antiseizure drugs used, and epilepsy duration. Significance: Our study supports the presence of ALF in a task of word recall among adult patients with GGE. The pattern of forgetting visuospatial information suggests greater forgetting of material before the first delay and ongoing deficits among PWEs with epileptic activity. Future studies should confirm our findings and investigate the functional or pathological mechanisms of memory dysfunction in GGE.